PERAN GENERASI MUDA DALAM MEWUJUDKAN MASYARAKAT PANCASILA DI SOCIAL SOCIETY - Rasyid, A.Ramli; Ananda, Warda Sri; Darwis, Nur Musfira; Ramadhan, Reski Rahmat (INSTITUT TEKNOLOGI DAN BISNIS INDOBARU NASIONAL, 2022)
Youth is the forerunner of a country's advanced order. The youth of a nation are ultimately responsible for its progress or lack thereof. This research is a type of qualitative research, using descriptive methods. The data analysis technique uses qualitative descriptive analysis, where this technique describes existing data and makes conclusions so that they are easily understood by themselves and others. The millennial generation is believed to be able to straighten out the direction of the country's development where this generation has the function of building positive character through a strong determination to uphold moral values and internalize real life.